Desenvolvimento, características morfoanatômicas e ecofisiológicas de Aphelandra nitida Ness & Mart. (acanthaceae) - Zottele, Livia (2017)
This study vegetative and sexual propagation were evaluated, and the post-seminal development, and the morphological and ecophysiological characteristics of Aphelandra nitida submitted to different gradients of shading. The fruits, seeds and stem cuttings were obtained in the Forest of Restinga located in the neighborhood Liberdade, São Mateus-ES. The biometry and morphology of fruits and seeds were analyzed, and germination tests were performed on different substrates. The vegetative propagation of the species was carried out with different types of cuttings in vermiculite substrate. After the formation of vegetative propagation, these were transferred to the structure covered with screens under different shading conditions, in which after the end of the experiment, the morphological and leaves echophysiological characteristics were evaluated. The fruit consists of a loculicidal capsule constituted by two leaflets, which open releasing the seeds. The 5% sodium hypochlorite concentration for 30 minutes is the most suitable for seed disinfestation. The use of the substrate on paper is recommended for the germination of the species. The information about the postseminal development, mainly the foliar characters, reinforces the characteristics found in adult plants, being these morphological characteristics of great importance to aid the taxonomic studies and to interpret germination tests. The results of vegetative propagation showed that the basal cuttings are the most suitable for propagation of the species, not being anatomical barriers that hamper the rooting in any of the types of cuttings. The shading conditions to which the plants were subjected strongly influenced the evaluated parameters. The plants were tolerant to the full sun, observing changes in the photosynthetic apparatus as the reduction in the photochemical efficiency, being compensated by a greater dissipation of heat and investing in structural adaptations, as the reduction of the leaf area, increase in the thickness of the palisade parenchyma, Increase in stomatal density and lipid compounds in mesophyll. The results of the present work highlight the importance of basic studies to understand the mechanisms involved in the propagation form, type of seed reserve, development and phenotypic plasticity of the species in relation to environmental conditions.